Covalent triazine framework temperature-responsive nanofiltration membranes, methods of making the same, and applications in lithium-selective separations

CN122643904BActive Publication Date: 2026-10-09ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611160825.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-09
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

[0005]传统纳滤膜在实际应用中存在以下短板:(1)通量与截留率之间的固有矛盾:提升水通量往往导致离子筛分能力下降,而追求高截留率则必须以牺牲通量为代价,这一trade-off效应使得现有纳滤膜在维持必要脱盐性能的条件下往往表现出较低的水通量,实际应用中不得不采用更大的膜面积和更高的操作压力;(2)膜污染与结垢问题:传统纳滤膜在运行过程中,溶质易吸附于膜表面及孔道内部,导致孔隙堵塞、通量衰减、截留率波动

Benefits of technology

(1)本发明基于CTF有机单体尺寸、对称性与连接方式的分子工程设计,结合界面聚合或层层自组装工艺,在支撑膜上制备具有亚纳米级规整孔径的薄层复合纳滤膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122643904B_ABST
    Figure CN122643904B_ABST
Patent Text Reader

Abstract

The application discloses a covalent triazine framework temperature-responsive nanofiltration membrane in the technical field of nanofiltration membranes, a preparation method thereof and application thereof in lithium selective separation, and relates to a covalent triazine framework temperature-responsive nanofiltration membrane, which comprises a support membrane and a separation layer arranged on the support membrane, wherein the separation layer comprises covalent triazine skeleton nanomaterial, polyethyleneimine (PEI) and a temperature-responsive polymer; the covalent triazine skeleton nanomaterial is synthesized into CTF-0 and CTF-NH nanomaterials, and is poured onto the surface of a PEI modified support membrane in sequence, and is constructed on the surface of the PEI modified support membrane through ultraviolet irradiation; the temperature-responsive polymer is grafted to the surface and / or the inner wall of pores of the separation layer, and the temperature-responsive polymer can reversibly change the segment conformation under temperature stimulation, so as to reversibly change the pore size and / or the hydrophilic-hydrophobic property of the separation layer; and the covalent triazine framework temperature-responsive nanofiltration membrane prepared by the application can simultaneously improve the flux and selectivity of the membrane and enhance the anti-pollution ability of the membrane, and provides a feasible path for the development of a next-generation high-performance self-adapting separation membrane material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofiltration membrane technology, specifically to a covalent triazine framework temperature-responsive nanofiltration membrane, its preparation method, and its application in the selective separation of lithium. Background Technology

[0002] Achieving highly selective enrichment and separation of lithium ions from complex secondary resources such as salt lake brines, lithium extraction mother liquor from ores, and spent lithium-ion batteries is a crucial step in ensuring lithium resource security and promoting the development of a circular economy. Traditional separation technologies, such as precipitation and solvent extraction, often suffer from problems such as long processes and limited selectivity. Therefore, developing a separation material and technology that combines high selectivity, high permeability flux, and excellent stability has significant application value.

[0003] Nanofiltration (NF) membranes are a type of pressure-driven membrane separation technology that falls between ultrafiltration (UF) and reverse osmosis (RO). Their separation performance primarily stems from the synergistic effect of pore size sieving and charge repulsion (Dornnan effect). This technology can selectively retain organic matter and multivalent ions of specific molecular weights while allowing some monovalent ions to permeate. The operating pressure is typically around 5 bar, offering the advantages of both high separation efficiency and low energy consumption.

[0004] Compared to amorphous polymer materials such as polyimide, polyamide, polyacrylonitrile, polyethersulfone, and polyvinylidene fluoride used in traditional nanofiltration membrane applications, porous organic polymers (including covalent organic frameworks, conjugated porous polymers, and porous aromatic polymers) exhibit significant advantages in separation applications due to their inherent permanent porosity, large pore volume, and excellent structural stability. Among them, covalent triazine frameworks (CTF), as a novel porous organic nanomaterial, are constructed with triazine rings as their structural core through strong aromatic covalent bonds. This not only endows the material with excellent chemical stability and abundant nitrogen-active sites but also allows for structural diversity and performance customization through the selection of different monomers. CTF possesses a regular and ordered molecular arrangement, high specific surface area, tunable pore size, and environmentally friendly properties. Its pore size can be precisely controlled through the size, symmetry, and connection mode of the organic linkers, making it suitable for precise molecular-size-based separation. These characteristics make CTF a highly promising functional material in the field of separation membranes, playing a crucial role in improving sieving accuracy, enhancing mass transfer efficiency, and strengthening membrane structural stability.

[0005] Traditional nanofiltration membranes have the following shortcomings in practical applications: (1) The inherent contradiction between flux and rejection rate: increasing water flux often leads to a decrease in ion sieving capacity, while pursuing a high rejection rate requires sacrificing flux. This trade-off effect makes existing nanofiltration membranes often exhibit low water flux under the condition of maintaining necessary desalination performance. In practical applications, larger membrane area and higher operating pressure must be used; (2) Membrane fouling and scaling problems: During operation, solutes are easily adsorbed on the membrane surface and inside the pores of traditional nanofiltration membranes, resulting in pore blockage, flux decay, and fluctuation in rejection rate. Meanwhile, the polyamide separation layer is electronegative in aqueous solution and can adsorb positive ions through electrostatic interaction, resulting in complex pollution among membrane, cations and organic matter. Membrane pollution not only shortens the service life of the membrane, but also significantly increases the operation and maintenance costs; (3) Traditional membrane materials have disordered structure and lack active regulation capabilities: Nanofiltration membranes are mostly made of amorphous polymers, such as polyimide, polyamide, polyacrylonitrile, polyethersulfone and polyvinylidene fluoride. Their disordered chain structure and low porosity limit the molecular sieving efficiency. Once the physicochemical properties of traditional membrane materials are determined, they cannot be changed. The membrane materials themselves do not have the ability to actively adjust the separation behavior and flux according to changes in the external environment; (4) CTF membrane flux is limited: The interlayer spacing of CTF nanosheets is relatively narrow and the hydrophilicity is poor. In practical applications, CTF membranes also face the trade-off between water flux and rejection rate; (5) The comprehensive performance of smart response nanofiltration membranes is not yet perfect: Most only focus on the regulation and optimization of single performance, and have not yet achieved a systematic synergistic improvement of membrane flux, selectivity and antifouling performance. Summary of the Invention

[0006] The purpose of this invention is to solve the above-mentioned technical problems by providing a covalent triazine framework temperature-responsive nanofiltration membrane, its preparation method, and its application in the selective separation of lithium.

[0007] The present invention achieves the above objectives through the following technical solutions: As a first aspect of the present invention, a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane is provided, comprising the following steps: (1) CTF-0 nanomaterials were synthesized by ionothermal method using 1,3,5-tricyanobenzene as a reactant monomer, and CTF-NH nanomaterials were synthesized by polycondensation reaction using 1,3,5-cyanuric chloride and p-phenylenediamine as reactants. CTF-0 nanomaterials and CTF-NH nanomaterials were dissolved in solvents respectively to obtain CTF-0 suspension and CTF-NH suspension. (2) The support film is modified by immersing it in PEI solution to obtain PEI modified support film. CTF-0 suspension and CTF-NH suspension are poured onto the surface of the PEI modified support film in sequence. After ultraviolet irradiation, CTF loaded film is obtained. The amine groups on the PEI molecular chain give the support film surface a positive charge, which enhances the subsequent electrostatic attraction of negatively charged CTF nanomaterials and / or polyvalent anions. At the same time as ultraviolet irradiation, the cross-linking reaction between CTF nanomaterials and PEI and the interfacial bonding reaction between PEI and support film are initiated, realizing the dual fixation of CTF nanomaterials on the support film surface by chemical anchoring and physical adhesive, which significantly enhances the interfacial bonding strength and anti-peeling performance of CTF loaded layer. (3) The CTF-supported membrane was sequentially immersed in an aqueous solution containing piperazine and an oil solution containing pyromellitic chloride to carry out interfacial polymerization reaction to obtain a CTF-PA nanofiltration membrane; (4) The CTF-PA nanofiltration membrane was immersed in DMAEMA solution and grafted polymerized under ultraviolet irradiation to obtain the covalent triazine framework temperature-responsive nanofiltration membrane.

[0008] As a further optimization of the present invention, in step (1), the preparation method of the CTF-0 nanomaterial is as follows: 1,3,5-Tricyanobenzene and zinc chloride or sodium chloride were added to an ampoule in a mass ratio of 1-5:6-10. After vacuum sealing, the ampoule was calcined at 300-600℃ for 20-50 hours. After grinding, washing with water, acid washing, washing with organic solvent and drying, CTF-0 nanomaterials were obtained.

[0009] As a further optimization of the present invention, in step (1), the preparation method of the CTF-NH nanomaterial is as follows: p-phenylenediamine and anhydrous sodium carbonate were dissolved in deionized water at a molar ratio of 7-9:2-4, and then mixed with an acetone solution containing 1-2 mmol of cyanuric chloride. The mixture was stirred at 20-30℃ for 10 h, and after centrifugation, washing and drying, CTF-NH nanomaterials were obtained.

[0010] As a further optimization of the present invention, in step (1), the solvent is at least one of deionized water, methanol or ethanol; The concentrations of both the CTF-0 suspension and the CTF-NH suspension are 0.5-10 g / L.

[0011] As a further optimization of the present invention, in step (2), the concentration of the PEI solution is 5-30 g / L and the soaking time is 3-15 min.

[0012] As a further optimization of the present invention, in step (3), the mass fraction of piperazine in the aqueous solution is 0.05-0.3wt%, and the soaking time is 1-4min; The oil phase solution contains 0.05-0.2 wt% pyromellitic chloroformyl chloride, and the soaking time is 1-3 min. The interfacial polymerization reaction was carried out at 55-65℃ for 2-5 minutes.

[0013] As a further optimization of the present invention, in step (4), the concentration of the DMAEMA solution is 5-40 g / L.

[0014] As a further optimization of the present invention, in steps (2) and (4), the process parameters of the ultraviolet irradiation are: the wavelength of the ultraviolet irradiation is 340-405nm, the irradiation time is 5-30min, and the irradiation distance is 10-20cm.

[0015] As a second aspect of the present invention, a covalent triazine framework temperature-responsive nanofiltration membrane is also provided, prepared by the method described in any of the preceding claims. The structure includes a support membrane and a separation layer located on the support membrane. The separation layer comprises a covalent triazine framework (CTF) nanomaterial, polyethyleneimine (PEI), and a temperature-responsive polymer. The PEI serves as an interfacial bonding layer between the support membrane and the CTF nanomaterial, used to fix the CTF nanomaterial to the surface of the support membrane, while simultaneously imparting positive charge properties to the separation layer. Specifically, the PEI anchors the CTF nanomaterial to the surface of the support membrane through electrostatic adsorption and / or hydrogen bonding, forming a CTF / PEI composite. A composite transition layer is formed; during subsequent interfacial polymerization, the composite transition layer forms an interpenetrating network structure with the polyamide active layer, enhancing the overall structural stability of the separation layer. Temperature-responsive polymers are grafted onto the surface and / or inner walls of the pores of the separation layer. Under temperature stimulation, these polymers undergo reversible changes in chain segment conformation, thereby driving reversible changes in the pore size and / or hydrophilicity / hydrophobicity of the separation layer. Specifically, below the minimum critical dissolution temperature (LCST) of the temperature-responsive polymer, the polymer chains extend, the membrane pore size decreases, and a high rejection rate mode is observed; above the LCST, the polymer chains contract and collapse, the membrane pore size increases, and a high flux mode is observed.

[0016] As a third aspect of the invention, the application of a covalent triazine framework temperature-responsive nanofiltration membrane as described above in the selective separation of lithium is also provided.

[0017] The beneficial effects of this invention are as follows: (1) Based on the molecular engineering design of CTF organic monomer size, symmetry and connection mode, this invention combines interfacial polymerization or layer-by-layer self-assembly process to prepare a thin-layer composite nanofiltration membrane with sub-nanometer regular pore size on a support membrane.

[0018] (2) This invention utilizes temperature as a purely physical stimulus signal to induce changes in the hydrophilicity and hydrophobicity of the membrane surface by adjusting the operating temperature. Under low temperature conditions, the hydrophilic temperature-sensitive segments extend, achieving a switch from high flux to high selectivity; under high temperature conditions, the segments contract and collapse, the membrane pores expand, and the water permeation flux is significantly improved. This mechanism achieves a dynamic balance and synergistic optimization of membrane flux and rejection rate under different operating conditions, alleviating the problem that traditional nanofiltration membranes cannot achieve both simultaneously.

[0019] (3) This invention utilizes the reversible hydrophilicity-hydrophobicity change characteristics of temperature-responsive materials before and after the phase transition temperature to endow the membrane surface with in-situ self-cleaning function. During operation, by periodically applying temperature change stimulation, organic pollutants attached to the membrane surface and pores are desorbed, significantly alleviating irreversible fouling and scaling problems, thereby effectively curbing flux decline during long-term operation and greatly extending the service life of the membrane.

[0020] (4) This invention optimizes the interfacial compatibility and dispersion process of CTF nanomaterials and thermosensitive polymers, and establishes the structure-property relationship between key parameters in the interfacial polymerization or layer-by-layer self-assembly process and the final performance of the membrane.

[0021] (5) The covalent triazine framework temperature-responsive nanofiltration membrane prepared by the present invention can simultaneously improve the membrane flux and selectivity while enhancing its antifouling ability, providing a feasible path for the development of next-generation high-performance adaptive separation membrane materials. Attached Figure Description

[0022] Figure 1 Scanning electron microscope (SEM) images of the surface morphology of the modified nanofiltration membrane provided by the present invention; wherein, Figure 1 (a) is a CTF nanofiltration membrane image; Figure 1 (b) is a high-magnification image of the CTF nanofiltration membrane; Figure 1 (c) is a CTF temperature response nanofiltration membrane image; Figure 1 (d) is a high-magnification image of the CTF temperature-response nanofiltration membrane.

[0023] Figure 2 SEM image of the cross-sectional morphology of the CTF temperature-response nanofiltration membrane provided by the present invention.

[0024] Figure 3 Fourier transform infrared spectral analysis of the CTF-0 nanomaterials provided in this invention.

[0025] Figure 4 Fourier transform infrared spectral analysis of the CTF-NF nanomaterials provided in this invention.

[0026] Figure 5The XRD spectra of CTF-0 and CTF-NH nanomaterials provided by this invention.

[0027] Figure 6 The CTF nanofiltration membrane and the CTF temperature-responsive nanofiltration membrane provided by the present invention have water contact angles at different temperatures.

[0028] Figure 7 The antifouling performance of the CTF temperature-responsive nanofiltration membrane prepared in Example 1 of this invention.

[0029] Figure 8 The differential charge model is used in the theoretical calculations of CTF-0 and CTF-NH nanomaterials with PEI molecular density functional theory (hereinafter referred to as DFT) provided by this invention.

[0030] Figure 9 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared by only changing the concentration of CTF material in Examples 1 to 4 of this invention were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart.

[0031] Figure 10 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared by only changing the PEI solution concentration in Examples 1, 5 to 7 of this invention were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart.

[0032] Figure 11 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared by only changing the concentration of DMAEMA solution in Examples 1, 8 to 10 of this invention were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart.

[0033] Figure 12 The CTF temperature-responsive nanofiltration membranes prepared in Examples 1, 11 to 13 of this invention, by only changing the UV irradiation time when grafting the temperature-responsive group DMAEMA, were subjected to water flux testing and separation performance testing, yielding water flux and magnesium-lithium separation factor values. The results are presented in a statistical chart.

[0034] Figure 13 The results of water flux test and ion rejection rate test of Comparative Examples 1 to 4, blank example and Example 1 provided by the present invention are compared. Detailed Implementation

[0035] The present application will now be described in further detail with reference to the accompanying drawings. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.

[0036] The present invention achieves the following technical solution through at least one typical embodiment: A method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane includes the following steps: Synthesis of S1, CTF-0 and CTF-NH nanomaterials (1) Synthesis of CTF-0 nanomaterials 1,3,5-Tricyanobenzene was selected as the monomer for the synthesis of CTF-0 nanomaterials. The specific synthesis steps are as follows: 1,3,5-Tricyanobenzene and zinc chloride or sodium chloride powder were weighed and added to an ampoule in a mass ratio of (1-5):(6-10) to seal the ampoule, ensuring it was in a sealed and vacuum state. The ampoule was then placed in a muffle furnace for high-temperature calcination at 300-600℃ for 20-50 hours. After calcination, the solid material was removed from the ampoule, ground into small pieces, and then a certain amount of deionized water was added. The mixture was stirred at 600 rpm for 11-14 hours in a water bath at 80-90℃. Subsequently, a 0.05-0.2M dilute hydrochloric acid solution was added and the mixture was stirred in a water bath at 80-90℃ for 11-14 hours. The solid is filtered out and washed 2-4 times with at least one of dimethyl sulfoxide, chloroform or acetone. Then it is vacuum dried at 80-90℃ for 10-15h to obtain CTF-0 solid, which is CTF-0 nanomaterial.

[0037] (2) Synthesis of CTF-NH nanomaterials CTF-NH was synthesized using 1,3,5-cyanuric chloride and p-phenylenediamine as monomers. The specific synthesis steps are as follows: p-phenylenediamine and anhydrous sodium carbonate powder were weighed and dissolved in deionized water at a molar ratio of (7-9):(2-4). Then, 1-2 mmol of cyanuric chloride powder was weighed and dissolved in 30 ml of acetone. The two solutions were mixed and stirred at 20-30℃ for 10 h. The solid and solvent were then separated by centrifugation at 8000±1000 rpm for 5-7 min. After centrifugation, excess solvent was discarded, and a certain volume of acetone was added and thoroughly mixed. Centrifugation was repeated 3-5 times. Then, a certain volume of methanol solution was added and centrifuged again 5-8 times (using the same centrifuge parameters). After centrifugation, the mixture was dried in an oven at 60-65℃ for 10-12 h to obtain CTF-NH solid, which is the CTF-NH nanomaterial.

[0038] Preparation of S2, CTF-0 suspension and CTF-NF suspension (1) Preparation of CTF-0 suspension Weigh 0.05-0.5g of CTF-0 solid, grind it thoroughly in a mortar into a uniform powder, transfer it to a beaker and add 30-50ml of deionized water, stir thoroughly to obtain a CTF-0 suspension with a concentration of 0.5-10g / L.

[0039] (2) Preparation of CTF-NF suspension Weigh 0.05-0.5g of CTF-NH solid, grind it thoroughly in a mortar into a uniform powder, transfer it to a beaker and add 30-50ml of methanol, ethanol or any other alcohol solvent, and stir thoroughly to obtain a CTF-NH suspension with a concentration of 0.5-10g / L.

[0040] Preparation of S3, piperazine solution and trimesoyl chloride solution Weigh 0.05-0.1g of piperazine solid, add a certain volume of deionized water, and prepare a piperazine solution with a mass fraction of 0.05-0.3wt% as the aqueous phase solution; weigh 0.01-0.04g of pyromellitic chloride powder, add a certain volume of n-hexane, and prepare a pyromellitic chloride solution with a mass fraction of 0.05-0.2wt% as the oil phase solution.

[0041] Preparation of S4 and CTF nanofiltration membranes Use a polyethersulfone (PES) substrate membrane as a support membrane, immerse it in a polyethyleneimine (PEI) solution with a concentration of 5-30 g / L for 3-15 min, remove it and fix it with a PTFE clamp; take 0.5-2 ml of CTF-0 suspension and drop it onto the surface of the PES substrate membrane, let it stand for 1-5 min, then drop an equal volume of CTF-NH suspension, gently shake it to make the CTF suspension spread evenly on the surface of the PES substrate membrane, place the membrane at a position of 15-20 cm under a UV lamp with a UV wavelength of 340-405 nm, and irradiate for 5-30 min.

[0042] After irradiation, discard excess solution and place the entire membrane in an oven at 50-60°C for 3-10 minutes to perform interfacial polymerization, adding a dense polyamide active layer to the membrane surface to achieve nanofiltration level. Remove the PTFE clamps and immerse the PES membrane loaded with CTF nanomaterials in a piperazine solution for 1-4 minutes. After removal, purge the membrane surface with nitrogen until no obvious water droplets remain. Then immerse the membrane in a trimesoyl chloride solution for 1-3 minutes, remove, and place in an oven at 55-65°C for 2-5 minutes to promote interfacial polymerization, ultimately obtaining a nanofiltration membrane loaded with CTF nanomaterials and a polyamide active layer, i.e., a CTF nanofiltration membrane.

[0043] S5, grafted smart response polymer A certain volume of dimethylaminoethyl methacrylate (DMAEMA) was added to deionized water and stirred until homogeneous, preparing a 30 ml DMAEMA solution with a mass concentration of 5-40 g / L. The CTF nanofiltration membrane was then completely immersed in the solution and placed under a UV lamp at a position of 15-20 cm with a UV wavelength of 340-405 nm for 5-30 min. After irradiation, the membrane was removed and immersed in 30 ml of anhydrous ethanol for 1-3 h to remove excess unreacted polymer. After immersion, the membrane was then placed in deionized water and washed with shaking for 5-10 min to obtain the DMAEMA-grafted CTF temperature-responsive nanofiltration membrane.

[0044] The CTF temperature-responsive nanofiltration membrane prepared by the above method consists of, from top to bottom, a PES substrate, a CTF material layer, an interfacial polymerization layer, and a smart temperature-responsive material layer. These three layers constitute the separation layer of the membrane. The CTF material layer and the interfacial polymerization layer make the membrane pore size comparable to the ion size, thereby providing physically small pore sizes to sieve lithium ions and other ions. At the same time, the CTF material layer has a considerable number of triazine functional groups, which have a stronger adsorption effect on high-valence ions and hinder the passage of other high-valence ions such as magnesium ions through the membrane, thus improving the separation of lithium ions from other ions. Furthermore, the membrane structure is regular rectangular or circular, with uniform thickness, smooth edges, and a total membrane thickness of 30 μm-200 μm.

[0045] The present invention will be described below through specific embodiments. It should be noted that the specific embodiments below are for illustrative purposes only and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods that do not specifically describe conditions or steps are conventional methods, and the reagents and materials used can be obtained commercially.

[0046] Example 1

[0047] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, comprising the following steps: Synthesis of S1 and CTF nanomaterials (1) Synthesis of CTF-0 nanomaterials 200 mg of 1,3,5-tricyanobenzene and 0.89 g of anhydrous ZnCl2 powder were weighed and thoroughly mixed in a mortar. The mixture was poured into an ampoule, which was then evacuated to a vacuum state and sealed to maintain a dry, vacuum-sealed interior. The mixture was heated at 400 °C for 40 h. After cooling, the material was removed and ground into powder. 50 ml of deionized water was added to the powder, and the mixture was vigorously stirred in a 90 °C water bath for 12 h. Then, 0.1 M dilute hydrochloric acid was added, and the mixture was vigorously stirred in a 90 °C water bath for 12 h to remove unreacted monomers and ZnCl2. The solid was filtered out and washed three times with deionized water, dimethyl sulfoxide, and acetone solutions, respectively. Finally, the mixture was vacuum-dried at 70 °C for 12 h to obtain CTF-0 nanomaterials.

[0048] (2) Synthesis of CTF-NH nanomaterials 7.49 mmol of p-phenylenediamine and 3 mmol of anhydrous sodium carbonate powder were weighed and dissolved in deionized water. Then, 2 mmol of cyanuric chloride powder was weighed and dissolved in 25 ml of acetone. The two solutions were mixed and stirred at 25 °C for 8 h. The solid and solvent obtained from the reaction were then separated by centrifugation at 8000 rpm for 5 min. After centrifugation, excess solvent was discarded and a certain volume of acetone was added and shaken thoroughly. The mixture was centrifuged again, and this process was repeated 3 times. Then, a certain volume of methanol solution was added and the mixture was centrifuged 5 times again (with the centrifuge parameters unchanged). After centrifugation, the mixture was vacuum dried at 60 °C for 12 h to obtain CTF-NH nanomaterials.

[0049] Construction of S2 and CTF nanofiltration membranes (1) After grinding CTF-0 nanomaterials into powder, deionized water was added to prepare a suspension with a concentration of 2 g / L. After grinding CTF-NH nanomaterials into powder, anhydrous ethanol was added to prepare a suspension with a concentration of 2 g / L. (2) After washing the PES membrane three times with deionized water, immerse it in a PEI solution with a concentration of 15 g / L for 10 min, and then clamp it in a PTFE clamp. (3) First, take 1 ml of CTF-0 suspension and pour it onto the PES membrane. Gently shake the membrane to spread the CTF-0 suspension evenly on the surface of the PES membrane. Let it stand for 2 minutes, then add 1 ml of CTF-NH suspension. Gently shake the membrane to spread the CTF-NH suspension evenly on the surface of the PES membrane. Let it stand for 2 minutes. (4) Place the membrane 15cm under a UV lamp, select a UV wavelength of 340nm, and irradiate for 25min. After irradiation, discard the excess solution. (5) Place the whole thing in an oven and dry for 2 minutes at a temperature of 60°C; (6) Remove the PTFE clamp, take out the PES membrane loaded with CTF material and immerse it in a 0.2 wt% piperazine solution for 3 min. After taking it out, blow the membrane surface with nitrogen until there are no obvious water droplets on the surface. (7) The membrane is then immersed in a 0.1 wt% solution of trimesoyl chloride for 2 min, and then placed in an oven to dry for 3 min at a temperature of 60°C to promote interfacial polymerization and obtain a CTF nanofiltration membrane.

[0050] S3, Grafting of temperature-responsive groups DMAEMA was added to deionized water and stirred until homogeneous to prepare a 20 ml DMAEMA solution with a concentration of 25 g / L. The CTF nanofiltration membrane obtained in step S2 was completely immersed in the DMAEMA solution and placed under a UV lamp at 15 cm with a UV wavelength of 340 nm for 5 min. After irradiation, the membrane was removed and immersed in 30 ml of anhydrous ethanol for 2 h to remove excess unreacted polymer. After immersion, the membrane was placed in deionized water and shaken for 7 min to obtain a DMAEMA-grafted CTF temperature-responsive nanofiltration membrane.

[0051] The CTF nanofiltration membrane and CTF temperature-responsive nanofiltration membrane prepared in Example 1 were tested for the following: (1) Observe the surface morphology of the film using SEM, such as Figure 1 The image shows the surface morphology of a CTF nanofiltration membrane and a CTF temperature-responsive nanofiltration membrane. The CTF nanomaterials are rectangular nanosheets that are alternately stacked on the membrane. After grafting temperature-responsive groups, the nanosheets become thinner and longer, resulting in a tighter connection between the CTF nanosheets on the membrane surface and forming a more compact structure. Figure 2 The image shows a cross-sectional topography of the CTF temperature-responsive nanofiltration membrane, where CTF forms large sheet-like structures on the membrane surface.

[0052] (2) Fourier transform infrared spectroscopy was used to determine the functional groups of CTF nanomaterials to observe whether CTF nanomaterials were successfully synthesized. Figure 3 The infrared spectrum of CTF-0 nanomaterials shows the presence of triazine functional groups and carbon-nitrogen triple bonds, which are unique to CTF-0 nanomaterials, proving that CTF-0 was successfully synthesized.

[0053] Figure 4 The infrared spectrum of CTF-NH nanomaterials shows that it possesses the unique functional groups triazine and carbon-nitrogen triple bonds, as well as secondary hydrogen functional groups, proving the successful synthesis of CTF-NH nanomaterials.

[0054] (3) The crystal properties of CTF nanomaterials were determined using X-ray crystal diffractometer (XRD). Figure 5 The XRD patterns of CTF-0 and CTF-NH nanomaterials are shown below, corresponding to the PDF card, proving that the materials were successfully synthesized.

[0055] (4) Water contact angle measurement: The water contact angle of the prepared CTF nanofiltration membrane and CTF temperature-responsive nanofiltration membrane at different temperatures was measured using a high-temperature contact measuring instrument. Figure 6 The figure shows the water contact angles of the CTF nanofiltration membrane and the CTF temperature-responsive nanofiltration membrane. After grafting the temperature-responsive group, the CTF temperature-responsive nanofiltration membrane exhibits hydrophilicity at room temperature (25°C), with a smaller water contact angle compared to the ungrafted CTF nanofiltration membrane. At high temperature (60°C), the CTF temperature-responsive nanofiltration membrane exhibits hydrophobicity, with a larger water contact angle compared to room temperature (25°C). This demonstrates that the temperature-responsive group was successfully grafted onto the CTF nanofiltration membrane and exhibits temperature responsiveness.

[0056] (5) Determination of ion rejection rate: The single ion rejection rate was determined using a conductivity meter. The feed solution was a single ion solution (MgCl2) with a concentration of 1000 ppm. 1 ml of ion feed solution and the filtered permeate were taken and diluted to 8 ml. The ionic conductivity of the two solutions was measured using a conductivity meter. The ion rejection rate R was calculated according to the following formula: ;

[0057] Where, σ p Permeate conductivity, σ f This indicates the conductivity of the feed liquid.

[0058] (6) Membrane separation performance was determined using ICP-AES: The feed solution was a mixed ionic solution with a total concentration of 2000 ppm and a mass ratio of MgCl2:LiCl = 20:1. 1 ml of the prepared ionic feed solution and 1 ml of the filtered permeate were taken and diluted to 10 ml. The concentrations of magnesium ions and lithium ions before and after filtration were tested using ICP-AES. The magnesium-lithium separation factor was calculated according to the formula. The calculation formula is as follows: ;

[0059] in, This represents the ratio of magnesium ion concentration to lithium ion concentration in the feed solution. This represents the ratio of magnesium ion concentration to lithium ion concentration in the permeate.

[0060] (7) Water flux measurement: The water flux of the membrane was tested using a cross-flow flat sheet membrane filtration device. The membrane permeation area was approximately 7 cm². 2The membrane permeation performance was evaluated. The filtration equipment was thoroughly cleaned and rinsed before the filtration experiments. Initially, the membrane was filtered for 1 hour at an operating pressure of 4 bar using deionized water as the feed solution to ensure membrane stability. Performance was then evaluated at 5 bar (unless otherwise specified), and the water flux was calculated using the following formula: ;

[0061] Where V represents the permeation volume (L); A represents the effective membrane area (cm²). 2 ); t represents filtration time (h); Δp represents operating pressure (bar).

[0062] (8) Anti-pollution test The antifouling performance of temperature-responsive nanofiltration membranes (CTF) was investigated using a cross-flow flat sheet membrane filtration system. The pollutant was bovine serum albumin (BSA) at a concentration of 500 ppm. The test consisted of three cycles: water flux measurement with deionized water, BSA contamination, and deionized water rinsing.

[0063] Using a conventional nanofiltration membrane (NF) as a control, the preparation method of the conventional nanofiltration membrane (NF) is as follows: the PES membrane is washed three times with deionized water and then immersed in a 0.2 wt% piperazine solution for 3 min. After taking it out, the membrane surface is purged with nitrogen until there are no obvious water droplets on the surface. Then the membrane is immersed in a 0.1 wt% trimesoyl chloride solution for 2 min. After taking it out, it is placed in an oven to dry for 3 min at a temperature of 60℃ to promote the interfacial polymerization reaction, so as to obtain a nanofiltration membrane with a polyamide active layer loaded on the surface.

[0064] The results are as follows Figure 7 As shown, the water flux of ordinary nanofiltration membranes gradually decreases under BSA fouling, and even after rinsing with deionized water, the water flux is difficult to recover. CTF temperature-responsive nanofiltration membranes have good hydrophilicity at low temperatures and high water flux, but their water flux also decreases significantly after BSA fouling. While the water flux recovers somewhat after rinsing, the overall trend remains downward, indicating that relying solely on the material's hydrophilicity is insufficient to remove BSA contaminants. When the CTF temperature-responsive nanofiltration membrane is rinsed at high temperature (60°C), the responsive polymer collapses and shrinks, becoming hydrophobic, making it difficult for BSA to continue adhering. After rinsing at high temperature (60°C), the water flux of the CTF temperature-responsive nanofiltration membrane essentially returns to its uncontaminated state, proving that the contaminants are basically completely removed.

[0065] (9) DFT simulation of the membrane separation layer: The calculation was performed using the ORCA 6.1.1 software package. Geometric optimization was performed at the GFN2-xTB level. The electron density difference was calculated using Multiwfn 2026.4.10, and the density difference visualization was performed using VESTA.

[0066] Figure 8 The figure shows the differential charge model in the theoretical calculations of the DFT of CTF-0 and CTF-NH nanomaterials with PEI molecules. The blue areas represent decreasing electron density, and the yellow areas represent increasing electron density. The polarization direction of charge transfer is very obvious. The triazine ring (containing electron-withdrawing N atoms) in the CTF structure exhibits a strong inductive effect, causing the electron clouds on the amino groups (-NH2 or -NH-) on the PEI chain to shift towards it. Due to the strong electronegativity of the nitrogen atom, the triazine ring of CTF exhibits a significant electron-rich (negatively charged) characteristic in and around the ring; while PEI contains a large number of amino groups (with partially positively charged hydrogen atoms). When the two come into contact, a strong Coulomb electrostatic attraction is generated. The amino group (-NH2) of PEI acts as a proton donor, and the exposed nitrogen atom in the CTF structure acts as a proton acceptor, spontaneously forming a dense network of hydrogen bonds at the interface. This hydrogen bonding is not only physical adsorption but also involves the transfer of some charge to form chemical bonds, greatly enhancing the stability of the composite material.

[0067] Example 2

[0068] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S2, the construction of the CTF nanofiltration membrane; in this embodiment, CTF-0 and CTF-NH materials are respectively prepared into suspensions with a concentration of 1 g / L. Other steps and parameters are the same as in Example 1.

[0069] Example 3

[0070] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S2, the construction of the CTF nanofiltration membrane; in this embodiment, CTF-0 and CTF-NH materials are respectively prepared into suspensions with a concentration of 3 g / L. Other steps and parameters are the same as in Example 1.

[0071] Example 4

[0072] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S2, the construction of the CTF nanofiltration membrane; in this embodiment, CTF-0 and CTF-NH materials are respectively prepared into suspensions with a concentration of 4 g / L. Other steps and parameters are the same as in Example 1.

[0073] Examples 2-4 were subjected to the same water flux test and separation performance test as in Example 1.

[0074] Figure 9 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared by only changing the CTF material concentration in Examples 1-4 were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart. Figure 9 It can be seen that the optimal concentration of CTF material is 2 g / L.

[0075] Example 5

[0076] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S2, the construction of the CTF nanofiltration membrane; in this embodiment, the concentration of the PEI solution is 5 g / L. Other steps and parameters are the same as in Example 1.

[0077] Example 6

[0078] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S2, the construction of the CTF nanofiltration membrane; in this embodiment, the concentration of the PEI solution is 10 g / L. Other steps and parameters are the same as in Example 1.

[0079] Example 7

[0080] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S2, the construction of the CTF nanofiltration membrane; in this embodiment, the concentration of the PEI solution is 20 g / L. Other steps and parameters are the same as in Example 1.

[0081] Examples 5-7 were subjected to the same water flux test and separation performance test as in Example 1.

[0082] Figure 10 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared by only changing the PEI solution concentration in Examples 1 and 5-7 were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart. Figure 10 It can be seen that the optimal concentration of PEI solution is 15 g / L.

[0083] Example 8

[0084] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S3, grafting of temperature-responsive groups; in this embodiment, the concentration of DMAEMA solution is 15 g / L. Other steps and parameters are the same as in Example 1.

[0085] Example 9

[0086] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S3, grafting of temperature-responsive groups; in this embodiment, the concentration of DMAEMA solution is 20 g / L. Other steps and parameters are the same as in Example 1.

[0087] Examples 8-10 were subjected to the same water flux test and separation performance test as in Example 1.

[0088] Figure 11 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared by only changing the concentration of DMAEMA solution in Examples 1 and 8-10 were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart. Figure 11 It can be seen that the optimal concentration of DMAEMA solution is 25 g / L.

[0089] Example 10

[0090] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S3, the grafting of temperature-responsive groups; in this embodiment, the concentration of the DMAEMA solution is 30 g / L. Other steps and parameters are the same as in Example 1.

[0091] Example 11

[0092] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S3, the grafting of temperature-responsive groups; in this embodiment, the ultraviolet lamp irradiation time is 2.5 min. Other steps and parameters are the same as in Example 1.

[0093] Example 12

[0094] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S3, the grafting of temperature-responsive groups; in this embodiment, the ultraviolet lamp irradiation time is 7.5 min. Other steps and parameters are the same as in Example 1.

[0095] Example 13

[0096] This embodiment provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: S3, grafting of temperature-responsive groups; in this embodiment, the ultraviolet lamp irradiation time is 10 min. Other steps and parameters are the same as in Example 1.

[0097] Examples 11-13 were subjected to the same water flux test and separation performance test as in Example 1.

[0098] Figure 12 The water flux and magnesium-lithium separation factor of the CTF temperature-responsive nanofiltration membranes prepared in Examples 1 and 11-13, which only varied the UV irradiation time when grafting the temperature-responsive group DMAEMA, were obtained through water flux testing and separation performance testing. The results are presented in a statistical chart. Figure 11It can be seen that the optimal UV irradiation time for grafting the temperature-responsive group DMAEMA is 5 minutes.

[0099] To further illustrate the effect of the preparation method provided by this invention on the performance of the prepared covalent triazine framework temperature-responsive nanofiltration membrane, the following comparative examples 1-4 are set up for comparison with Example 1: Comparative Example 1 The comparative example provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that S2 and the construction of the CTF nanofiltration membrane are performed. This comparative example only adds CTF-0 suspension and does not add CTF-NH suspension. Other steps and parameters are the same as in Example 1.

[0100] Comparative Example 2 The comparative example provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that S2 and the construction of the CTF nanofiltration membrane are performed. This comparative example only adds CTF-NH suspension and does not add CTF-0 suspension. Other steps and parameters are the same as in Example 1.

[0101] Comparative Example 3 This comparative example provides a method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, which differs from Example 1 in that: this comparative example does not perform grafting of S3 and temperature-responsive groups. Other steps and parameters are the same as in Example 1.

[0102] Comparative Example 4 The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane provided in this comparative example differs from Example 1 in that, in step S2, the construction of the CTF nanofiltration membrane is as follows: the PES membrane is washed three times with deionized water and then directly sandwiched into a PTFE clamp without immersing it in a 15 g / L PEI solution. Other steps and parameters are the same as in Example 1.

[0103] Blank example The comparative example provides a method for preparing a conventional nanofiltration membrane, which involves washing the PES membrane three times with deionized water, immersing it in a 0.2 wt% piperazine solution for 3 minutes, removing it, and then purging the membrane surface with nitrogen until there are no obvious water droplets on the surface; then immersing the membrane in a 0.1 wt% trimesoyl chloride solution for 2 minutes, removing it, and then drying it in an oven at 60°C for 3 minutes to promote interfacial polymerization reaction, thereby obtaining a nanofiltration membrane with a polyamide active layer loaded on its surface.

[0104] Comparative Examples 1-4 and blank examples were subjected to the same water flux and ion rejection rate tests at room temperature as in Example 1.

[0105] The results are as follows Figure 13As shown, compared to the blank example, both the comparative examples and the embodiment showed improvements in salt rejection rate and water flux. Comparative example 1 had the highest salt rejection rate, but its water flux remained at a low level with almost no improvement. Comparative example 2 had a significantly improved water flux, but its salt rejection rate decreased. Combining comparative examples 1 and 2, it can be seen that the combined CTF-0 and CTF-NH nanomaterials can produce a membrane with both high salt rejection rate and water flux. In addition, the order of addition of CTF-0 and CTF-NH nanomaterials has an impact on the successful construction of the membrane. In practice, after the PES membrane is soaked in PEI in the first step, a large number of amino groups (which are naturally present on the PEI chain) will be grafted onto its surface. The hydrolysis of amino groups can generate abundant positive charges, which can attract the purely negatively charged CTF-0 nanomaterials. The CTF-NH nanomaterials also have secondary hydrogen groups and are negatively charged. In water, they will form strong hydrogen bonds, van der Waals forces, and electrostatic attraction with PEI. Adding CTF-NH first will cause most of the PEI on the membrane to bind with CTF-NH. The CTF-0 nanomaterial added later has only negative charge and no other active functional groups, resulting in less binding with PEI, poor stability, and easy detachment, making it impossible to successfully construct the membrane.

[0106] Comparative Example 3 showed a significant decrease in water flux after PEI modification due to the dense and adhesive properties of PEI. However, the overall stability of the modified membrane was greatly improved. It remained stable for a long time under water flow impact with very little material falling off, and the material distribution on the membrane surface was more uniform. Comparative Example 4 introduced a responsive material. Due to its hydrophilic properties, the water flux was greatly increased, but the salt retention effect was weakened at the same time. Combining Comparative Examples 3 and 4, the membranes were modified with PEI and temperature response to improve both water flux and salt retention rate, thus addressing the trade-off between the increase in water flux and the decrease in salt retention rate.

[0107] Based on comparative examples 1-4, the modified membrane was finally prepared according to the steps of Example 1. It maintained a high water flux and a high magnesium chloride rejection rate, which played an important role in breaking the balance between water flux and salt rejection rate in separating magnesium and lithium ions.

[0108] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane, characterized in that, Includes the following steps: (1) CTF-0 nanomaterials were synthesized by ionothermal method using 1,3,5-tricyanobenzene as a reactant monomer, and CTF-NH nanomaterials were synthesized by polycondensation reaction using 1,3,5-cyanuric chloride and p-phenylenediamine as reactants. CTF-0 nanomaterials and CTF-NH nanomaterials were dissolved in solvents respectively to obtain CTF-0 suspension and CTF-NH suspension. (2) The support membrane is modified by immersing it in PEI solution to obtain a PEI-modified support membrane. CTF-0 suspension and CTF-NH suspension are poured onto the surface of the PEI-modified support membrane in sequence and then treated with ultraviolet light to obtain a CTF-loaded membrane. (3) The CTF-supported membrane was sequentially immersed in an aqueous solution containing piperazine and an oil solution containing pyromellitic chloride to carry out interfacial polymerization reaction to obtain a CTF-PA nanofiltration membrane; (4) The CTF-PA nanofiltration membrane was immersed in DMAEMA solution and grafted under ultraviolet irradiation to obtain the covalent triazine framework temperature-responsive nanofiltration membrane.

2. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In step (1), the preparation method of the CTF-0 nanomaterial is as follows: 1,3,5-Tricyanobenzene and zinc chloride or sodium chloride were added to an ampoule in a mass ratio of 1-5:6-10. After vacuum sealing, the ampoule was calcined at 300-600℃ for 20-50 hours. After grinding, washing with water, acid washing, washing with organic solvent and drying, CTF-0 nanomaterials were obtained.

3. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In step (1), the preparation method of the CTF-NH nanomaterial is as follows: p-phenylenediamine and anhydrous sodium carbonate were dissolved in deionized water at a molar ratio of 7-9:2-4, and then mixed with an acetone solution containing 1-2 mmol of cyanuric chloride. The mixture was stirred at 20-30℃ for 10 h, and after centrifugation, washing and drying, CTF-NH nanomaterials were obtained.

4. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In step (1), the solvent is at least one of deionized water, methanol, or ethanol; The concentrations of both the CTF-0 suspension and the CTF-NH suspension are 0.5-10 g / L.

5. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In step (2), the concentration of the PEI solution is 5-30 g / L, and the soaking time is 3-15 min.

6. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In step (3), the mass fraction of piperazine in the aqueous solution is 0.05-0.3wt%, and the soaking time is 1-4 min; the mass fraction of trimesoyl chloride in the oil solution is 0.05-0.2wt%, and the soaking time is 1-3 min. The interfacial polymerization reaction was carried out at 55-65℃ for 2-5 minutes.

7. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In step (4), the concentration of the DMAEMA solution is 5-40 g / L.

8. The method for preparing a covalent triazine framework temperature-responsive nanofiltration membrane according to claim 1, characterized in that, In steps (2) and (4), the process parameters for ultraviolet irradiation are: the wavelength of ultraviolet irradiation is 340-405nm, the irradiation time is 5-30min, and the irradiation distance is 10-20cm.

9. A covalent triazine framework temperature-responsive nanofiltration membrane, characterized in that, It is prepared by the method described in any one of claims 1-8.

10. The application of a covalent triazine framework temperature-responsive nanofiltration membrane as described in claim 9 in the selective separation of lithium.

Citation Information

Patent Citations

  • Polyamide composite membrane with asymmetric double-layer structure as well as preparation method and application of polyamide composite membrane

    CN115990411A

  • Multilayer composite structure diaphragm

    CN116780113A